2015
DOI: 10.3923/ajpsaj.2015.85.96
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Boron Supplementation and its Impact on Semen Characteristics and Physiological Status of Adult Male Rabbits

Abstract: This study was carried out to assess the effect of Boron supplementation on male rabbit's reproductive performance. A total of 20 V. Line (V.L) adult rabbit bucks were divided into four equal experimental groups (5 bucks for each). Groups 2, 3 and 4 were fed rations supplemented with 17.5, 35 and 70 mg boron/kg feed in the form of boric acid (100, 200 and 400 mg boric acid, respectively) over 8 weeks. The first group was served as a control group. Results obtained by the Boron groups revealed that adding Boron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…On the other hand, the percentage of abnormal sperm was significantly decreased with increasing boron level to reach, and % less than the control group. These results are in agreement with Elkomy et al (2015) who concluded that adding boric acid to bucks' ration (100, 200 and 400 mg/kg) improved semen quality characteristics.…”
Section: Biochemical Parameterssupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, the percentage of abnormal sperm was significantly decreased with increasing boron level to reach, and % less than the control group. These results are in agreement with Elkomy et al (2015) who concluded that adding boric acid to bucks' ration (100, 200 and 400 mg/kg) improved semen quality characteristics.…”
Section: Biochemical Parameterssupporting
confidence: 92%
“…The same finding was found by El-Saadany et al (2016) when they fed male chicks on 100, 200 and 300 mg boron/kg feed. Likewise, our findings were confirmed upon examination of boron on rabbits (Elkomy et al, 2015). As a result, supplemental boron had a beneficial effect on hens' health.…”
Section: Biochemical Parameterssupporting
confidence: 80%
See 2 more Smart Citations
“…The RT was measured by using clinical thermometer, which inserted for 1 min into the rectum for about 2 cm from anus orifice after liniment by pure Vaseline (Khalil et al, 2014). The TSL was measured in terms of reaction time in seconds and was estimated between introducing the teaser doe to the buck's cage up to the point, when the buck started to mount the doe (Elkomy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%